ASYNCHRONOUS INFORMATION DISTRIBUTION AND CLUSTER STATE SYNCHRONIZATION - NABOŻNY, Maciej (Applied Computer Science, 2018)
This article describes issues related to information distribution and cluster state synchronization in environments with inconsistent network topology (with partially connected nodes or disconnected), without centralized authentication and authorization points. The main objective of this study was to create a set of rules and functional requirements to build a framework for building applications in decentralized and distributed environments that are not fully fault-tolerant, regardless of the underlying cluster’s hardware topology and availability. These solutions are based on selected principles known from the Blockchain database, Public Key Infrastructure, and Event Driven Development. Functional requirements derived from these systems are the basis of a framework dedicated for creating decentralized systems and distribution of information, used in systems developed by cloudover.io company together with AGH University of Science and Technology. Proposed principles were implemented as free library – libdinemic, which is base for future cluster management system, dedicated for large and inconsistent environments.